Injury in the young - Platt, M. P. Ward 1954-; Little, R. A. (Cambridge University Press, 1998)
This book describes the underlying mechanisms and pathophysiological processes which relate to various childhood injuries, and brings together experimental and empirical data which bear on the rational management of injury in childhood. It also deals with the wider issues of service organization and rehabilitation. The book describes the commonest causes and types of injury encountered in the young, including trauma, head injury, near drowning and burns. It also deals with essential aspects of effective management of injury in the hospital including trauma scoring, life support and nutritional support. It is intended for trainees and consultants in paediatrics, paediatric surgery, accident and emergency, anaesthesia and intensive care, and it will also serve as a source book for medical and non-medical researchers